Apr 8, 2021 Thread starter #1 karush Well-known member Jan 31, 2012 2,886 source Change the second-order IVP into a system of equations $y''+y'-2y=0 \quad y(0)= 2\quad y'(0)=0$ let $u=y'$ ok I stuck on this substitution stuff

source Change the second-order IVP into a system of equations $y''+y'-2y=0 \quad y(0)= 2\quad y'(0)=0$ let $u=y'$ ok I stuck on this substitution stuff

Apr 8, 2021 #2 C Country Boy Well-known member MHB Math Helper Jan 30, 2018 731 Since y'= u, y''= u' so y''+ y'- 2y= u'+ u- 2y= 0 so u'= 2y-u.